Effects of Water‐Washed Biochar on Soil Properties, Greenhouse Gas Emissions, and Rice Yield. Issue 4 (12th February 2018) - Lu, Haohao; Wang, Yaofeng; Liu, Yuxue; Wang, Yuying; He, Lili; Zhong, Zheke; Yang, Shengmao
Abstract : Biochar application might be a newly agricultural method for improving soil quality and carbon sequestration by its special physical and chemical properties, which has generated great interest for scientists and policy makers. However, the physical structure of biochar and its effect on N2 O and CH4 emissions are not yet clear. The effect of bamboo biochar and water‐washed bamboo biochar with or without N fertilization on greenhouse gas emissions, soil properties, and rice yield in a pot experiment were investigated. The results showed that biochar application increased soil pH, total N content, dissolved organic carbon (DOC), and rice plant growth. Although biochar application increased DOC content, N2 O and CH4 emissions decreased. The soil N H 4 + and N O 3 − contents were significantly decreased by biochar application, indicating that bamboo biochar has a remarkable ability to absorb N H 4 + and N O 3 − . However, no significant differences in N2 O emission were observed between biochar and washed biochar treatment. The CH4 emission in the washed biochar treatment was decreased to a greater extent than in the unwashed biochar, indicating that washed biochar has a greater inhibitory effect on CH4 emission than does unwashed biochar, and that the stable physical structure of biochar might be an important factor for reducing CH4 emissions. Additional studies are needed to investigate the role of functional microorganism in order to better understand the biochar on greenhouse gas emissions from paddy soils. Abstract : The present study shows that N2 O and CH4 emissions decrease by biochar application in paddy soil. The washed biochar has a greater inhibitory effect on CH4 emission than does unwashed biochar, and the stable physical structure of biochar may be an important factor for reducing CH4 emissions.